Complete response of cutaneous SCC to topical treatment with ascorbic acid solution: A case report. Issue 3 (9th January 2021) - Pernice, Carmine; Murri, Domenico; Valli, Riccardo; Crocetta, Francesco M.; Iori, Michele; Asti, Mattia; Ghidini, Angelo; Capponi, Pier C.
Abstract: Clinical use of topical ascorbic acid solution could have both the role as an adjunct to consolidated therapies and as an alternative to them, for the treatment of BCC and SCC of the skin. Abstract : Clinical use of topical ascorbic acid solution could have both the role as an adjunct to consolidated therapies and as an alternative to them, for the treatment of BCC and SCC of the skin.